THE DOCTRINE OF SEPARATION OF POWERS UNDER THE NIGERIAN CONSTITUTION: Received: 01st Sept 2021; Revised: 05th July 2022, 22nd July 2022, 26th July 2022; Accepted: 26th August 2022 - Nwauzi, Linus O (PEOPLE: International Journal of Social Sciences, 2022)
Separation of powers is a hallowed constitutional principle of the democratic government of Nigeria for the three arms of government to stay in their assigned tracks to avoid arbitrary excesses by any of the arms. The ideal is that the legislature makes the law; the executive executes the law, while the judiciary interprets the law. In recent times, the president of Nigeria churns out Executive Orders in the form of ‘laws seeking to regulate the activities of the government and the people. Similarly, agencies of the federal government have been found wanting in this act. This paper thus revisits the doctrine of separation of powers in Nigeria with a view to justifying its practice and an examination of the emerging trends of Executive Order and independence of the judiciary. The paper finds that the practice of separation of powers is on course in Nigeria despite some pockets of arbitrariness and concludes that adherence to the principles of separation of powers remains a sine qua non to Nigeria’s successful democratic journey.